Comportamento de mudas de nim à salinidade da água em solo não salino com biofertilizante - Nunes, Jarisson C.; Cavalcante, Lourival F.; de Lima Neto, Antonio J. [UNESP]; Rebequi, Alex M.; Diniz, Belisia L. M. T.; Gheyi, Hans R. (Universidade Federal da Paraíba (UFPB) Ccsa, 2012)
An experiment was carried out in greenhouse during the period January to April 2010, at Center of Agricultural Sciences of the Federal University of Paraiba, in Areia, Paraiba State, Brazil, in order to evaluate the effects of saline water and bovine biofertilizer on the seedling growth of Indian neem. The substrate was material of a non-saline soil collected in depth of 0-20 cm. The treatments were arranged in a completely randomized design using a 5 x 2 factorial, referring to salinity levels of irrigation water of 0.5, 1.0, 2.0, 3.0 and 4.0 dS m(-1), with and without bovine biofertilizer applied to the soil only once after dilution with water (1: 1), a day before sowing, in volume corresponding to 10% of the substrate. At 86 days after emergence of seedlings the plant growth in height and principal root length, diameter of stem and root, leaf number and dry mass of roots and shoots of plants were evaluated. The salinity of irrigation water increased the salinity levels in the substrate inhibiting the growth in height, stem diameter, leaf emission by plants, diameter and length of principal root and the dry matter production of roots and aerial parts (leaves + stem) of neem, but with less pronounced decrease in plants under the treatments with bovine biofertilizer.
Behavior of neem seedlings under water salinity in a non-saline soil with biofertilizer application
Keywords: Azadirachta indica; saline stress; Organic manure